2017
DOI: 10.1002/prp2.353
|View full text |Cite
|
Sign up to set email alerts
|

Lack of clinically important PK interaction between coformulated ledipasvir/sofosbuvir and rilpivirine/emtricitabine/tenofovir alafenamide

Abstract: The drug–drug interaction (DDI) potential between the fixed‐dose combinations of ledipasvir/sofosbuvir 90/400 mg for hepatitis C virus and emtricitabine/rilpivirine/tenofovir alafenamide (TAF) 200/25/25 mg for HIV was evaluated in a randomized, open‐label, single‐center, multiple‐dose, 3‐way, 6‐sequence, crossover Phase 1 study in 42 healthy subjects. Emtricitabine/rilpivirine/TAF had no relevant effect on the pharmacokinetic parameters of maximum concentration [C max] and area under the concentration versus t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 13 publications
2
7
0
Order By: Relevance
“…https://doi.org/10.1371/journal.pone.0224875.g003 combined with either E/C/F/TAF or R/F/TAF regimens. Furthermore, this study confirmed pharmacokinetic data in healthy volunteers showing no clinical risk of renal toxicity when either boosted (E/C/F/TAF) or unboosted (R/F/TAF) TAF-based regimens were co-administered with 12 weeks of LDV/SOF [21]; there were minimal changes seen in eGFR CG and improvements in urinary protein markers for participants receiving both regimens.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…https://doi.org/10.1371/journal.pone.0224875.g003 combined with either E/C/F/TAF or R/F/TAF regimens. Furthermore, this study confirmed pharmacokinetic data in healthy volunteers showing no clinical risk of renal toxicity when either boosted (E/C/F/TAF) or unboosted (R/F/TAF) TAF-based regimens were co-administered with 12 weeks of LDV/SOF [21]; there were minimal changes seen in eGFR CG and improvements in urinary protein markers for participants receiving both regimens.…”
Section: Discussionsupporting
confidence: 78%
“…Since tenofovir alafenamide (TAF) has 80-91% lower plasma TFV concentrations than TDF, the renal safety of concomitant treatment with LDV/SOF may be improved with TAF compared to TDFbased regimens [20]. Two phase 1 studies in healthy participants evaluated DDIs between LDV/SOF and two F/TAF-based antiretroviral therapy (ART) regimens: rilpivirine/emtricitabine/TAF (R/F/TAF) or elvitegravir/cobicistat/emtricitabine/TAF (E/C/F/TAF) [21,22]. LDV/SOF co-administered with R/F/TAF modestly increased plasma TFV exposure, however, TFV area under the curve (AUC) levels remained substantially lower than TFV exposures from TDF-containing regimens (362 vs 2000-5000 ng.h/mL; R/F/TAF + LDV/SOF vs R/F/ approved compounds or indication the IPD will be available for request 6 months after FDA and EMA approval.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, while an interaction is possible, there has been no short‐term evidence of clinical consequences. While exposure increases 1.4‐fold when coadministered with boosted DRV, this is not considered clinically significant …”
Section: Arv Interactions With Hepatitis B and C Treatmentmentioning
confidence: 95%
“… 14 A study on the effect of food on Taf pharmacokinetics showed that Taf exposure decreased in fasting conditions. 15 However, no significant trend in exposure response/safety regarding Taf exposure was found in fasting or fed conditions. 11 …”
Section: Drv-cobi-ftc-taf Pharmacokineticsmentioning
confidence: 96%
“…It also lacks the induction activity of Rtv on several enzymes and transporters, including CYP isoenzymes, Pgp, and glucuronyltransferases. 15 , 31 , 32 …”
Section: Drv-cobi-ftc-taf Pharmacokineticsmentioning
confidence: 99%